A study of the critical velocity and the confinement velocity of fire accident in a longitudinally ventilated underground train with different door opening scenarios. (January 2023) - Su, Zhihe; Li, Yanfeng; Feng, Shan; Zhong, Hua; Li, Junmei; Liu, Wenbo; Chen, Chao; Li, Jiaxin
Highlights: Door opening scenarios for a metro train fire were studied. A theoretical model for the inner carriage smoke propagation was developed. Experiments were conducted for smoke control of a metro train carriage inner fire. Critical velocities and confinement velocities of two door opening scenarios were proposed. Abstract: The critical velocity, confinement velocity and smoke back-layering length are significant factors for smoke control in a tunnel fire. This research aims to analysis the correlation of these 3 key smoke control parameters in the different door opening scenarios during a fire in the metro train carriage that stopped in the tunnel. Scaled model experiment measurement and numerical simulations were carried out for the propagation and control of smoke. Five fire locations in the train and two side doors opening scenarios of the train were considered. Results show that smoke back-layering length in the train can be barely influenced by the activation time of the longitudinal ventilation system. However, the opening of side doors could result in a shorter smoke back-layering length in the train. Furthermore, we present a dimensionless correlation for the critical velocity and confinement velocity of underground train fires caused by fires in the double-length narrow space of an underground tunnel. This study provides a predictive model for the design of smoke control systems for fire of train stopped in underground tunnels.